2012
DOI: 10.1155/2012/835903
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis Key Features Mining and Patients Clustering Technologies

Abstract: The kidneys are very vital organs. Failing kidneys lose their ability to filter out waste products, resulting in kidney disease. To extend or save the lives of patients with impaired kidney function, kidney replacement is typically utilized, such as hemodialysis. This work uses an entropy function to identify key features related to hemodialysis. By identifying these key features, one can determine whether a patient requires hemodialysis. This work uses these key features as dimensions in cluster analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Some studies reported that ANN and other data mining methods supported medical decisions regarding VUR and some nephrological problems (21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that ANN and other data mining methods supported medical decisions regarding VUR and some nephrological problems (21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…This is useful since some poor variables in this respect might be abandoned in future research if they do not provide useful information for medicine. Variable or feature evaluation and selection is an important phase in data analysis, as in, for example, [14,15], because it is necessary to find which variables most affect classification and also those which are less influential. If there are a particularly large number of variables, variable selection is important.…”
Section: Introductionmentioning
confidence: 99%